Turning to international litigation to protect the Amazon?. Issue 2 (17th December 2020) - Bendel, Justine; Stephens, Tim
Abstract: Safeguarding the Amazon biome remains a critical priority, not only for the eight Amazon River basin States but also for the world at large given the ecosystem's planetary importance. There is now a new sense of urgency surrounding Amazon protection given the substantial increase in rates of deforestation and fires in the region. Accordingly, new options to advance Amazon protection are beginning to be explored, including proceedings in international courts and tribunals. This article provides a critical assessment of the potential for such litigation, examining the possible claims that could be advanced, the risks associated with each of these and which are more likely to be successful. It argues that the litigation landscape is complex, and there are jurisdictional, normative and evidentiary hurdles in the way of a clear‐cut judgment requiring Amazon States to take the urgent and direct measures needed to bring the ecosystem back from the brink.